Ethnicity and the Colonial State Finding and Representing Group Identifications in a Coastal West African and Global Perspective (1850-1960) - Keese, Alexander (Studies in Global Social History, 2015)
Ethnicity and the Colonial State compares the choices of community leaders in three different West African groups (Wolof, Temne, and Ewe), with regard to "selling" their identifications to the colonial rulers. The book thereby addresses ethnicity as a factor in global history. Readership: Readers interested in themes of African history in the context of global history; academic libraries; students (undergraduate and postgraduate) of global, transnational, African history; students of social anthropology; and everyone interested in a critical discussion of ethnicity as an element of identification.